The WEF Nexus Journey - Mohtar, Rabi H. (Frontiers in Sustainable Food Systems, 2022)
This paper describes the beginning of the WEF Nexus Journey in the classroom and shows how the Nexus emerged into the discipline that it is today. The paper offers definitions, shares some success stories from around the world, reflects on future opportunities, and provides a few concluding remarks.